The effect of different grass-legume mixtures on nitrogen excretion of grazing sheep - Molle G.; Giovanetti V.; Cabiddu A.; Cuccureddu M.; Sitzia M.; Decandia M. (Nutritional and foraging ecology of sheep and goats, 2009)
A three-year study was carried out to assess the effect of different grass-legume mixtures on the N excretion of grazing Sardinian sheep in early-mid lactation (January-May). Replicate groups rotationally grazed plots of three grass-legume mixtures consisting of common grass (Lolium rigidum, Gaudin) and different legumes, namely: Medicago polymorpha (burr medic, treatment BM), Trifolium subterraneum (subclover, treatment SC) and Hedysarum coronarium (sulla, treatment SU). Herbage dry matter intake and faecal dry matter excretion were estimated by the n-alkane method in three sheep per replicate group on three or two occasions per year. The N content in herbage and faeces was measured in freeze-dried samples collected on the same occasions. N excretion in urine was estimated by difference, assuming no changes in body N while N utilisation efficiency (NUE) was calculated as the ratio between the yield of N in milk and N intake (NI). In years 1 and 3, corresponding to a higher proportion of legumes in sheep diet, SU groups showed higher N concentration and excretion in faeces and higher proportion of N in faeces as compared to the other groups (P < 0.05). In contrast, in the same years, BM resulted in a higher N excretion in urine (P < 0.05) and lower NUE (P < 0.05). Pooling all data (n = 72) NUE was negatively correlated with NI (r = -0.804, P < 0.001) and dietary N content (r = -0.654, P < 0.001). To conclude, the forage legume in the grass-legume mixture affected N excretion, its partitioning between urine and faeces and NUE.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)